2008
DOI: 10.1507/endocrj.k07e-089
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Albumin is a Better Indicator for Glucose Excursion than Glycated Hemoglobin in Type 1 and Type 2 Diabetes

Abstract: Abstract. To determine the impact of blood glucose profile, involving fluctuation and excursion of blood glucose levels, on glycated proteins, we evaluated the association among the daily profile of blood glucose, and glycated albumin (GA) and HbA1c levels in patients with type 1 diabetes (n = 93) and type 2 diabetes (n = 75). GA levels were strongly correlated with HbA1c levels in type 1 (r = 0.85, P<0.0001) and type 2 diabetes (r = 0.61, P<0.0001), respectively. HbA1c levels were similar between patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(166 citation statements)
references
References 20 publications
7
153
4
2
Order By: Relevance
“…As limitations of this study, both GA and the GA/ A1C ratio are reported to be affected by diabetes type [19][20][21][22] and obesity [20,[22][23][24]. A similar tendency was also reported for the G-gap [6,7].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…As limitations of this study, both GA and the GA/ A1C ratio are reported to be affected by diabetes type [19][20][21][22] and obesity [20,[22][23][24]. A similar tendency was also reported for the G-gap [6,7].…”
Section: Discussionsupporting
confidence: 71%
“…However, given that approximately 50% of A1C is produced during the 30-35 days prior to measurement, both GA and A1C are affected by any significant alteration in plasma glucose during this period. The GA/A1C ratio may thus reflect worsening or improving fluctuations in glycemic control over the short term [21,22]. Some previous authors have argued that a high GA/A1C ratio is associated with postprandial glucose excursion, early progression to insulin therapy in type 2 diabetes, or other events [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that glycosylated serum proteins or glycated albumin (GA) is a better marker for evaluating glucose excursion in diabetes than HbA1c. 12,13 However, few studies have evaluated the association between FA and postprandial hyperglycemia or glycemic fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to A1C, GA is more suitable to monitor the beginning of drug therapy in DM (55), and also to control the dose and change of medication (51), since its levels diminish faster than A1C in intensive treatment (19). Paroni and cols.…”
Section: Ga In Glucose Monitoringmentioning
confidence: 99%